Hospital practice in times of COVID-19: Perceptions of midwifery interns in Peru, 2020 - Rojas-Silva, Jessica (2021)
Introduction: Participations of obstetric interns in hospital practice are relevant to strengthen professional skills and their future job development. However, this was affected by COVID-19, making it necessary to reflect the national reality to contribute to better university management. Objective: To explore the perception of obstetric interns regarding hospital practices in times of COVID-19 in Peru during 2020. Materials and Methods: Qualitative approach study with phenomenological design where 80 obstetric interns, representatives of each hospital headquarters, from different regions of Peru. The interviews were carried out in April 2020. An in-depth interview was applied where the perception of hospital practices was addressed according to: Current problems and solution proposals. The bioethical criteria in research were met. Results: Obstetric interns have been removed from hospital practices, mainly due to the absence of personal protective equipment and health insurance, economically affecting rent and food payments; Likewise, various universities did not offer solution proposals to the delay of the internships, generating concern in the delay of administrative procedures, even more so in students from undergraduate universities. Among the proposals, those who are close to graduating suggest being exempted from the months where there were no activities, in order not to delay future processes such as tuition and rural service; likewise, suspend the payment of these fees and strengthen knowledge through the discussion of virtual clinical cases. Conclusions: The cessation of hospital practice responds to a lack of guarantees in the health care of the student, generating economic repercussions and a negative perception regarding university management. Finally, solutions are reported that could be considered for the next decisions made by the institutions.